Systematic Literature Review: A Study of Academic Burnout among Undergraduate Students in Universities - Atika Rahmania El Barusi; Farida Kurniawati (International Journal of Science Education and Cultural Studies, 2024)
Research on burnout has flourished within the educational environment or academic settings, with academic burnout gaining significant attention in recent decades. This systematic review aims to synthesize evidence from previous studies regarding the depiction and influencing factors of burnout among undergraduate students. The search strategy adhered to the PRISMA guidelines and was based on the following keywords: "burnout," "academic," "college," "undergraduate." Using five online databes, namely Scopus, PubMed, Taylor & Francis Online, ScienceDirect, and EBSCOhost, were 20 articles were obtained. The findings show that academic burnout undergraduate can be affected by internal and external factors. Academic burnout can have serious implications for students' well-being and academic performance, and it may also impact their mental health. This study provides recommendations for future research on the importance of addressing and preventing academic burnout among undergraduate students.